Post-stroke depression: Outcome following rehabilitation - CHAN, Keen Loong (Institutional Knowledge at Singapore Management University, 1995)
Objective: This prospective study looks at the outcome of rehabilitation on mood and physical recovery in patients with post-stroke depression.Methods: Fifty-two patients in a rehabilitation centre were assessed for depression, modified Barthel' s score and Hamilton Rating Scale for depression on admission to and discharge from the rehabilitation centre. Aphasic, demented and delirious patients were excluded.Results: Fifty-five percent of the patients were assessed to have depression on admission and 98% had physical impairment. At the time of discharge, only 28.6% were depressed and two-thirds had improved in physical function. Patients with ail degrees of functional impairment showed equal improvement and there was no difference between Barthel' s scores for patients whose mood improved and those who remained depressed. There were very strong associations between functional assessment and depression, functional assessment on discharge with depression on admission, and patients' mood on admission and discharge. Depressed patients did not stay longer in the rehabilitation centre than non-depressed patients. Low doses of anti-depressants did not have an impact on mood or functional improvement.Conclusion: We have found that depression might not have a clear negative impact on rehabilitation, that mood improved at the end of rehabilitation and that the degree of depression on admission was a good predictor of the outcome of final physical impairment.